2021
DOI: 10.1200/jco.2021.39.15_suppl.4012
|View full text |Cite
|
Sign up to set email alerts
|

RATIONALE 302: Randomized, phase 3 study of tislelizumab versus chemotherapy as second-line treatment for advanced unresectable/metastatic esophageal squamous cell carcinoma.

Abstract: 4012 Background: Tislelizumab (tisle) monotherapy or plus chemotherapy demonstrated antitumor activity in patients (pts) with solid tumors, including esophageal squamous cell carcinoma (ESCC) (NCT03469557 and CTR20160872). Methods: In this global phase 3 study (NCT03430843), adults with histologically confirmed advanced/unresectable or metastatic ESCC whose disease progressed following prior systemic therapy with ≥1 evaluable lesion per RECIST v1.1 and an Eastern Cooperative Oncology Group performance score (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 0 publications
4
43
0
3
Order By: Relevance
“…In PD-L1+ patients who received tislelizumab, the median overall survival was 10.3 months vs. 6.8 months for those who received chemotherapy (HR 0.54, 95% CI: 0.36–0.79, P = 0.0006). 109 …”
Section: Antibody Therapeutics Undergoing First Regulatory Review In the Us Or Eumentioning
confidence: 99%
“…In PD-L1+ patients who received tislelizumab, the median overall survival was 10.3 months vs. 6.8 months for those who received chemotherapy (HR 0.54, 95% CI: 0.36–0.79, P = 0.0006). 109 …”
Section: Antibody Therapeutics Undergoing First Regulatory Review In the Us Or Eumentioning
confidence: 99%
“…The RATIONALE 302 trial investigated tislelizumab versus chemotherapy as secondline treatment and found that tislelizumab clinically and significantly improves the OS (median OS: 8.6 versus 6.3 months; HR 0.70; 95% CI 0.57-0.85, p = 0.0001) [46]. These promising novel drugs underline the potential of further investigation of immunotherapeutic agents.…”
Section: Esophageal Squamous Cell Carcinomamentioning
confidence: 99%
“…Another notable study in the second-line setting is RATIONALE 302, which was recently presented at ASCO 2021 [ 39 ]. In this global, phase 3 study, patients with esoSCC who had advanced/unresectable or metastatic disease and progression after first-line systemic chemotherapy were randomized to receive either tislelizumab (200 mg IV every 3 weeks) or investigator-chosen chemotherapy.…”
Section: The Use Of Ici In the Second-line Settingmentioning
confidence: 99%
“…Results for CPS < 10 tumors were not shown. Survival benefit was consistently observed across pre-defined subgroups and regions [ 39 ].…”
Section: The Use Of Ici In the Second-line Settingmentioning
confidence: 99%